Clinically unquestionable but histologically deceptive melanomas in acral skin grafts: PRAME confirms its role. (17th July 2022) - Santandrea, Giacomo; Valli, Riccardo; Ragazzi, Moira; Castagnetti, Fabio; Lai, Michela; Longo, Caterina; Piana, Simonetta
Abstract : The aim of this study was to investigate the role of PRAME in reducing the risk of an underestimation of tumour margins, in a consecutive series of acral melanomas recurring on skin grafts.